ANALISIS STRATEGI PENINGKATAN MOTIVASI KERJA PEGAWAI DI DPMPTSP KARAWANG - Mulia Manda Masyhuroh; Dedi Mulyadi; Sungkono Sungkono (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to analyze strategies for increasing employee work motivation at the One Stop Integrated Services and Investment Service (DPMPTSP) Karawang Regency. Employee work motivation is a key factor in improving service quality and work efficiency at DPMPTSP Karawang. Qualitative and quantitative approaches were used in this research by analyzing data from surveys, interviews and documentation studies.The research results show that strategies for increasing employee work motivation at DPMPTSP Karawang can be carried out through implementing training and development programs, providing fair rewards, increasing communication and openness, as well as sustainable promotions. Factors that encourage employee work motivation include existence, connectedness, self-actualization, and achievement. Meanwhile, factors that hinder work motivation are various internal disturbances and external threats that befall employees.